Influência das tecnologias digitais no processo de escrita da língua portuguesa - Martins, Eder da Silveira (2021)
The present study has as its theme to about language in messages exchanged via instant messaging applications. As a research question: what is the impact of the use of instant messaging applications in the writing of the Portuguese language? Its general purpose is to analyze academic research seeking to verify whether they point out how instant messaging applications - ICQ, MESSENGER, TWITTER, WHATSAPP, INSTAGRAN - influence the language structure in the writing of the Portuguese language. It has as theoretical basis the studies of Barton and Lee (2015) on online language and Laurence Bardin (2011) with the Content Analysis Theory as methodological scope. The research in question is constituted by means of a bibliographic survey of academic studies that investigated language mediated by digital technologies. Therefore, it is a qualitative research of bibliographic and exploratory characteristics, as it focuses on the analysis of data from academic studies that discuss online language. In the methodological procedure, the corpus was defined as Academic Papers from the Capes repository that dealt with subjects related to Instant Communication Applications. The selected papers were presented, observing the order in which the applications were created and not the year in which they were presented. Fifteen papers related to instant messaging applications were found and analyzed, 4 of them were discarded for not providing satisfactory answers to what was established in the analysis categories, and finally 11 papers were selected. These were searched in the Capes repository and chosen through the theme: "Interaction in Instant Messaging Applications", within a time span of 10 years, between 2010 and 2020. Through the analysis of the academic papers selected and presented in the methodology, it was proven the hypothesis that the language in the applications directly influences the structure of the language in the writing of the language and this changes from the resource (application) chosen for interaction. Moreover, it was also proven through the analysis the impact of the use of instant messaging applications on the writing of the Portuguese language.